If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2 + -3x + -3 = 8 Reorder the terms: 2 + -3 + 4x + -3x = 8 Combine like terms: 2 + -3 = -1 -1 + 4x + -3x = 8 Combine like terms: 4x + -3x = 1x -1 + 1x = 8 Solving -1 + 1x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 1x = 8 + 1 Combine like terms: -1 + 1 = 0 0 + 1x = 8 + 1 1x = 8 + 1 Combine like terms: 8 + 1 = 9 1x = 9 Divide each side by '1'. x = 9 Simplifying x = 9
| x^4+x^3-2x-2=0 | | 3x+2=9y | | 2d+8=28 | | 5x-5=2(3x-1)-2(x+3)+7 | | 9-4x=15-12x | | 18=4 | | 4+7x=6x-7 | | 5t+7=20 | | 70-5x=3x+18 | | 7x^2+x-3=0 | | 9-8x=55-22x | | 4x^2+61x+180=0 | | -15-11y=-9-3y | | 3(x+4)=2(2x-5)+13 | | 8x-1=11+4x | | 5(2x+7)=25 | | 6-7x=46-14x | | 15x^2-28+5=0 | | h^2+10h=-21 | | 5(x-6)+6=7(x+2)-6 | | 3x+8=-62-7x | | 5x+10=11-4x | | 6.4=x+3.7 | | 2x^2+13x+33=12 | | -16t+t+0=0 | | 4x-16=2x+2 | | -4t^2+t+0=0 | | -[9z-(15z+3)]=3+(5z+4) | | 0.5x-4+2x=5 | | b^2-7b-18=0 | | 2[k-(4k+13)+3]=2(k+10) | | 2x-4+2x=5 |